Effect of residual soil depth on soil-water characteristic curve and unsaturated shear strength - Tikno, Nickanor (2018)
Residual soils are derived from weathering of rock and are commonly found in unsaturated condition. The depth of residual soil highly influences the variability found in residual soil properties. However, there are few quantification works that have been carried out on residual soil properties in terms of depth. This study focused on investigating characteristics of residual soils from three main formations in Singapore from different depths with respect to parameters of soil-water characteristic curve (SWCC) and unsaturated shear strength using statistical analyses. The parameters investigated in this study are percentage of fines (%), air-entry value (AEV), saturated permeability (ks), effective cohesion (c’), effective friction angle (’) and angle representing the rate of increase in shear strength with respect to an increase in matric suction (b). The analysis in this study was carried out using statistical analysis with boxplot method, where each parameter was plotted in accordance with depth. Furthermore, five-parameter logistic (5PL) curve was chosen as best-fitting function to develop envelopes, such as upper limit, typical and lower limit, with reference to the boxplot. The results of the analyses indicated that the shape of percentage of fines plots influences the shape of plots in other parameters. It can be concluded that soils located at greater depth are composed of lesser fine particles which produce higher saturated permeability (ks), effective friction angle (’) and b. Furthermore, soils with lesser amount of fine particles correspond to lower air-entry value (AEV) and effective cohesion (c’). The percentage of fines plots clearly show the transition region between two layers which is denoted with steep gradient. Based on observation, convergence between upper and lower limits found in the percentage of fines plots of residual soils from Sedimentary Jurong Formation (SJF) and Bukit Timah Granite (BTG) is also observed in the AEV plots of respective soils. In addition, similarity between residual soils from SJF and Old Alluvium (OA) found in the percentage of fines plot at depths less than two meter might be accounted for the similarity found between ks plots for the corresponding soils at depths less than two meter. The analysis shows that typical value of c’ plot from BTG converges to 5 kPa at greater depths, which is the lowest among residual soils from other formations. This can be explained with the fact that soils in BTG is generally coarser in nature compared to soils from other formations. Subsequently, the values of b in the best-fit plot can be estimated visually to be half from the values in ’. This observation is in agreement with the previous study where the value of b was found to be about half of ’. Finally, the study found out that anisotropy ratio of hydraulic conductivity was observed in the data from laboratory experiment. This complements the previous study of hydraulic anisotropy ratio conducted on compacted soil specimen. As a result, future study should quantify hydraulic anisotropy ratio in undisturbed samples from residual soils.